2012
DOI: 10.1007/s10393-012-0754-x
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic Transmission of Tuberculosis Between Pastoralists and Their Livestock in South-East Ethiopia

Abstract: Despite huge global efforts in tuberculosis (TB) control, pastoral areas remain under-investigated. During two years sputum and fine needle aspirate (FNA) specimens were collected from 260 Ethiopian pastoralists of Oromia and Somali Regional States with suspected pulmonary TB and from 32 cases with suspected TB lymphadenitis. In parallel, 207 suspected tuberculous lesions were collected from cattle, camels and goats at abattoirs. All specimens were processed and cultured for mycobacteria; samples with acid-fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
85
5
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 34 publications
(57 reference statements)
11
85
5
4
Order By: Relevance
“…Humans suffering from active TB are the most probable source of M. tuberculosis in animals, with infection spread via sputum, and rarely urine or feces (Thoen and Steele, 1995) or respiratory route as in rural area of Ethiopia, grazing cattle are commonly brought into the farmer's households at night where they may become infected via aerosol transmission from humans . Previous studies in Ethiopia had confirmed transmission of M. tuberculosis from farmers to their cattle, goat, and camel ( Ameni et al, 2011;Gumi et al, 2012;Mamo et al, 2012) supporting the result of our study. Even though human to cattle transmission of M. tuberculosis has been reported, it is generally held that disease in cattle due to M. tuberculosis is less severe than that caused by M. bovis ,and the identification of M. tuberculosis in cattle by itself is intriguing (Tsegaye et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Humans suffering from active TB are the most probable source of M. tuberculosis in animals, with infection spread via sputum, and rarely urine or feces (Thoen and Steele, 1995) or respiratory route as in rural area of Ethiopia, grazing cattle are commonly brought into the farmer's households at night where they may become infected via aerosol transmission from humans . Previous studies in Ethiopia had confirmed transmission of M. tuberculosis from farmers to their cattle, goat, and camel ( Ameni et al, 2011;Gumi et al, 2012;Mamo et al, 2012) supporting the result of our study. Even though human to cattle transmission of M. tuberculosis has been reported, it is generally held that disease in cattle due to M. tuberculosis is less severe than that caused by M. bovis ,and the identification of M. tuberculosis in cattle by itself is intriguing (Tsegaye et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…In this regard, there exist studies that demonstrate that the M. tuberculosis find in the ranching it's a reflection of the situation of tuberculosis in human beings in such regions (30)(31)(32). This finding puts…”
Section: Discussionmentioning
confidence: 93%
“…M. bovis strains were also isolated by Donchenko et al (1975) in Russia from bulked samples of raw dromedary milk. Recent studies in Ethiopian abattoirs also reported isolation of M. bovis (Mamo et al, 2011) and M. tuberculosis from tissue lesions (Gumi et al, 2012;Zerom et al, 2012). Five to twelve percent abattoir-based prevalence of tuberculosis compatible lesions (TCL) in dromedary camels slaughtered at Dire Dawa abattoir in Eastern Ethiopia and in Addis Ababa abattoir were recorded (Mamo et al, 2009;Mamoet al, 2011;Zerom et al, 2012).…”
Section: Introductionmentioning
confidence: 99%